Epidemiological analysis of emergency ophthalmic cases in a specialist hospital in Tianjin - LI Xin; YU Feiping (Yanke Xuebao)
[Objective:] To analyze the disease spectrum of emergency cases at an ophthalmology hospital in Tianjin, offering evidence-based support for standardizing diagnostic procedures and rationing emergency medical resources. [Methods:] Reviewed clinical data of patients at the hospital's emergency department from January 2019 to December 2023, covering demographics, visit timings, seasonal distribution, and preliminary diagnoses. [Results:] A total of 26,077 ophthalmology emergency patients were included, with a male-to-female ratio of 1.12:1 and an average age of 36.82±15.44 years. Most patients were aged <14 years (26.74%) and 31~40 years (21.03%). Daily visits peaked at 10:00—12:00 (11.06%), 14:00—16:00 (10.41%), and 20:00—22:00 (10.43%), and were lowest at 05:00—07:00 (4.83%). April had the fewest visits (3.87%), August the most (11.61%), and summer accounted for the highest quarterly proportion (31.74%). The top 10 preliminary diagnoses were led by conjunctivitis (39.58%) and xerophthalmia (14.32%). Compared to 2019, the top 10 preliminary diagnoses dropped significantly in 2020 and 2021 (both P<0.001), 2020 95%CI(-0.98—-0.68),2021 95%CI(-0.54, -0.11). Similarly, these diagnoses were significantly lower in summer, autumn, and winter than in spring (all P<0.001), summer 95%CI(-0.32, -0.08), autumn 95%CI (-0.39, -0.14), winter 95%CI(-0.54, -0.30). In conjunctivitis cases, winter incidence was significantly lower than in spring and summer (both P<0.001). Gender distribution in the top 10 diagnoses was statistically significant (P<0.001), 95%CI(-0.08, -0.03)and (-0.08, -0.04). Compared to those aged <14, other age groups showed a downward trend in the top 10 preliminary diagnoses (all P<0.001), 14~20 95%CI(-0.88, -0.43), 21~30 95%CI(-1.01, -0.65), 31~40 95%CI(-1.10, -0.82), 41~50 95%CI(-0.97, -0.66), 51~60 95%CI(1.71,-1.38), 61~70 95%CI(-1.45, -1.08), 71~80 95%CI(-1.36, -0.80), >80 95%CI(-1.44,-0.22). [Conclusions:] Ophthalmology emergency patients are mainly children and middle-aged men, with those <14 years old at higher risk. Visit times follow a"three-peak-one-valley" pattern. Most diagnoses are non-urgent conditions like conjunctivitis and xerophthalmia.Conjunctivitis shows marked seasonality, peaking in spring and summer. Total ophthalmology emergency visits declined in 2020 and 2021 versus 2019, particularly for conjunctivitis and xerophthalmia, partially recovering in 2022.